2001
DOI: 10.1128/aem.67.11.5285-5293.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Colonization and In Planta Nitrogen Fixation by a Herbaspirillum sp. Isolated from Wild Rice Species

Abstract: Nitrogen-fixing bacteria were isolated from the stems of wild and cultivated rice on a modified Rennie medium. Based on 16S ribosomal DNA (rDNA) sequences, the diazotrophic isolates were phylogenetically close to four genera: Herbaspirillum, Ideonella, Enterobacter, and Azospirillum. Phenotypic properties and signature sequences of 16S rDNA indicated that three isolates (B65, B501, and B512) belong to the Herbaspirillum genus. To examine whether Herbaspirillum sp. strain B501 isolated from wild rice, Oryza off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
302
4
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 422 publications
(336 citation statements)
references
References 33 publications
9
302
4
12
Order By: Relevance
“…Analyzing this agricultural scene and given the importance of this nutrient, studies that evaluate N-fixing bacteria, regarding their alternative supply of this nutrient, are an important sustainable method in agriculture (Elbeltagy et al, 2001;Guimarães et al, 2007) and can promote yield increments, which is very important because, for upland rice in the Central-West region of Brazil (3,203 kg ha -1 ), for example, is relatively lower than that of the irrigated system (6,798 kg ha -1 ) obtained in the south of the country (CONAB, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing this agricultural scene and given the importance of this nutrient, studies that evaluate N-fixing bacteria, regarding their alternative supply of this nutrient, are an important sustainable method in agriculture (Elbeltagy et al, 2001;Guimarães et al, 2007) and can promote yield increments, which is very important because, for upland rice in the Central-West region of Brazil (3,203 kg ha -1 ), for example, is relatively lower than that of the irrigated system (6,798 kg ha -1 ) obtained in the south of the country (CONAB, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed at identifying the major physiological traits of the dominant rice-colonizing microorganisms and addressed the following research questions specifically: (1) how similar or different is the overall phyllosphere microbiota of this monocotyledonous tropically grown plant compared with the biota of the previously analyzed plant species; (2) is there evidence for microbial proteins specific for life in the phyllosphere and rhizosphere; (3) which are the potentially dominating catabolic processes of microorganisms living in association with rice, in particular in relation to onecarbon compound conversion; (4) to what extent can nitrogen fixation potential be demonstrated, considering the fact that phyllosphere bacteria and, even more so, stem endophytes have been reported to be able of nitrogen fixation, and rice is known to be colonized by diazotrophs (Elbeltagy et al, 2001;Elbeltagy and Ando, 2008;Fü rnkranz et al, 2008;Pedraza et al, 2009). Figure 1 Overview of samples analyzed in the present study and the applied methods to get insight into the identity and physiology of the rice-associated microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…It was motile and showed pectinase and cellulase activities. 14) Although the nitrogen fixation activity of Azospirillum sp. B510 was detected in vitro, the nitrogen contribution of this strain to plant growth was very low (less than 1%) (Isawa et al, unpublished data).…”
mentioning
confidence: 99%
“…12) Azospirillum, free-living nitrogen fixing rhizobacteria found in close association with plant roots and stems, is a well-studied genus of plant growth promoting bacteria (PGPB) that have beneficial effects on plants, such as increasing crop yield. 13,14) A recent study indicated that tomato plants inoculated with Azospirillum brasilense showed enhanced disease resistance against a virulent bacterial pathogen, Pseudomonas syringae pv. tomato.…”
mentioning
confidence: 99%